“The Mole on His Penis Lassos Her:” Cultural Understandings of Coercive Control and Emotional Abuse of Women in Cambodia - Eisenbruch, Maurice (Violence against women, 2024)
Throughout world history, moles and birthmarks have occupied a special place as omens. Little is known of the cultural beliefs concerning the determinants of coercive control. In this ethnographic study of coercive control in Cambodia, the focus is on popular beliefs that moles are omens portending that men shall control women. Lachrymal moles (under the eye) signify women weeping as a result of misery. Penile moles portend men attracting, controlling, even abusing women. They have implications for reinterpreting an “insider” view of hegemonic masculinity and for culturally responsive interventions against gender-based violence.